Impact of the bowel‐screening programme on the diagnosis of colorectal cancer in Ayrshire and Arran. (20th December 2012) - Roxburgh, C. S. D.; McTaggart, F.; Balsitis, M.; Diament, R. H.
Abstract Aim Bowel screening aims to reduce colorectal‐cancer mortality by the detection and treatment of early‐stage asymptomatic disease and the removal of precancerous adenomas. Bowel screening started in Ayrshire and Arran in September 2007. We report the impact of this screening on the diagnosis and stage of colorectal cancer and characterize screen‐detected cancers in comparison with those diagnosed through other pathways. Method Diagnoses were identified from an audit database. Referrals were grouped into screen detected, routine, urgent and emergency presentations. Results Between January 2001 and December 2010, 2289 diagnoses of colorectal cancer were made. From 2001 to 2006, the mean (range) number of new colorectal‐cancer diagnoses per year was 210 (198–220). Between 2007 and 2010, the mean (range) number of diagnoses per year was 256 (239–274), a significant (P = 0.008) increase. Since September 2007, 877 colorectal cancers have been diagnosed: 17% were screen detected; 11% were detected as a result of routine GP referral; 51% were detected after urgent GP referral; and 21% were emergency presentations. TNM stage increased with urgency of referral. Approximately two‐thirds (66%) of screen‐detected colorectal cancers were node negative vs 25% of emergency presentations (P < 0.001). Most screen‐detected cancers were distal to the splenic flexure (75%). Screened cancers had favourable pathology; lower T and N stages (both P < 0.001), less venous invasion (P < 0.001) and better differentiation (P < 0.05). Similar results were seen after stratification for TNM stage. Screening has not yet resulted in a significant shift towards early‐stage disease since 2007. Conclusion Screening has been associated with an increase in the numbers of both new and early‐stage colorectal cancers. Screen‐detected cancers are predominantly early‐stage disease with favourable pathology. At present, it remains to be seen whether screening will ultimately translate into an overall reduction in advanced‐stage disease.